The Crucial Role Of Mathematics In Enhancing Understanding Across Disciplines In Higher Education - Shobha.V (Elementary Education Online, 2023)
In the vast landscape of higher education, mathematics emerges as a universal language that transcends disciplinary boundaries. Its intrinsic value lies not only in its direct applications within fields like physics and computer science but also in its profound influence on the understanding of diverse subjects. This article delves into the indispensable role of mathematics in comprehending various disciplines within higher education and highlights how it serves as a bridge connecting seemingly disparate realms.